2001
DOI: 10.1046/j.1360-0443.2001.961115896.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use, drug use and alcohol‐related problems among men who have sex with men: the Urban Men's Health Study

Abstract: The complex pattern of associations with heavy and/or problematic substance use among urban MSM suggests that heavy and/or problematic substance use is grounded in multiple levels: the individual, the interpersonal and the socio-cultural.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
392
10
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 531 publications
(438 citation statements)
references
References 25 publications
30
392
10
6
Order By: Relevance
“…Consistent with prior research documenting the role of alcohol/drug use and elevated sexual risk among MSM, 45,46 substance use during sex was significantly associated with unprotected sex among Black MSM across different partner types. Participants who used poppers at least weekly during sex with a male partner were more likely to have engaged in serodiscordant sex in the prior year.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with prior research documenting the role of alcohol/drug use and elevated sexual risk among MSM, 45,46 substance use during sex was significantly associated with unprotected sex among Black MSM across different partner types. Participants who used poppers at least weekly during sex with a male partner were more likely to have engaged in serodiscordant sex in the prior year.…”
Section: Discussionsupporting
confidence: 83%
“…Interviews covered a range of social, psychological, and behavioral phenomena related to HIV. Major sections of the survey instrument included questions about the gay community (involvement, services used, attitudes toward) (Barrett & Pollack, 2005), demographic characteristics (Catania et al, 2006), attendance at gay venues ("places where men go to meet and socialize with other men") Woods et al, 2003), sexual behavior (both a "global" and partner-by-partner assessment), sexual development, including the "coming out" process (Barrett, Pollack, & Tilden, 2002), experiences with harassment and violence (including adverse familial events, anti-gay victimization, sexual coercion, and partner violence) (Arreola, Neilands, Pollack, Paul, & Catania, 2005;Greenwood et al, 2002;Relf, Huang, Campbell, & Catania, 2004),sexual problems, depression, and suicidal ideation (Mills et al, 2004;Paul et al, 2002), substance use (Klitzman, Greenberg, Pollack, & Dolezal, 2002;Stall et al, 2001aStall et al, , 2003, HIV testing and serostatus (Osmond et al, 2000;Stall et al, 2001b), and AIDS care-giving.…”
Section: Methodsmentioning
confidence: 99%
“…Among the most common items selected for analysis are total number of partners within a time period (usually one year or less) (e.g., Greenwood et al, 2001), total number of "one night stands" within a time period ("had sex with men with whom sex only happened once"; e.g., Stall et al, 2001a), and episodes of unprotected anal intercourse (e.g., Osmondet al, 2007). The last measure, unprotected anal intercourse, has been operationalized in multiple ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These PB are said to be depression, violent victimisation, substance abuse, alcohol, psychiatric disorders, psychological distress, lower perceived social support (Berlan et al, 2010;King et al, 2008;Meyer , 2003;Cochran et al, 2003;Cochran and Mays, 2000;Gilman et al, 2001., Marshal et al, 2008Mimiaga et al, 2009a;b;Safren and Heimberg, 1999;Stall et al, 2001;Chesney et al, 2003;The EXPLORE Study Team, 2004;Herbst et al, 2005). Although some studies have shown how substance use and high risk of HIV transmission are correlated (Stall et al, 2001;Hirshfield et al, 2004), most recent studies are now focussing on how 'syndemic'-a situation where these diverse psychosocial issues could interact to enhance HIV risky behaviour among MSM (Mustanski et al, 2007;Stall et al, 2008;Centers for Disease Control and Prevention, 2010). However, varieties of cognitive behavioural interventions have been studied and validated for the treatment of mood and anxiety disorders (Barlow, 2008) behavioural activation therapy and HIV risk reduction counselling in MSM who abuse crystal methamphetamine .…”
Section: Horizontal (Heterosexual) Transmissionmentioning
confidence: 99%